PKM KELOMPOK IBU RUMAH TANGGA PEDULI KESEHATAN JIWA DI KELURAHAN BANGKINGAN KECAMATAN LAKARSANTRI SURABAYA - Pandeirot M. Nancye; Aristina Halawa (STKIP PGRI Sidoarjo, 2018)
Mental health problems do not directly cause death but are very influential in reducing ability. The reality in lower-level communities there are still cases (diseases) that are not handled which ultimately lead to death, whether due to factors of family and community knowledge about low health, including the minimum community participation in overcoming mental health problems. In Bangkingan District, Lakarsantri Surabaya sub-district is a rural area in Surabaya which is very dense and complex in character of the population, and the initial data obtained 7 PWMD clients that need attention, so the number of potential social problems and mental disorders will also be high or increase . The problems in RW 01 and RW 03 are 7 PWMD patients, 34% of community members who are at risk of psychosocial problems. Housewives who have great potential in caring for family members who experience psychiatric problems have not been able to support the mental health of family members and have not been able to treat PWMD in the family, even though there are some PWMD in their area. The purpose of this community service activity is to solve the problems that exist in Partners, among others are 1) The lack of understanding and knowledge of housewives about concern for mental health, 2) The ability, skills and participation of the community do not have the role of caring and caring for People With Mental Disorders (PWMD) and 3) Do not have guidelines / guidelines for effective ways to treat PWMD. Solving problems by helping to provide solutions based on agreement with partners, namely building capacity (knowledge, skills and attitudes) of the community through housewives with training and mentoring activities in an effort to improve community mental health in Bangkingan Village, Lakarsantri District. The method used in this community service activity is education and training, field practice, socialization followed by assistance to housewives and families who have PWMD. The indicator of its success is an increase in knowledge capability, skills that support care for mental health problems and the ability to improve mental health in a society that we call the Standby Mental Health Village.